2022
DOI: 10.1038/s41598-022-24696-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term body tactile stimulation reduces aggression and improves productive performance in Nile tilapia groups

Abstract: One concern of the Anthropocene is the effects of human activities on animal welfare, revealing the urgency to mitigate impacts of rearing environments. Body tactile stimulation (TS), like massage therapy, has emerged as an enrichment method to counteract stress and anxiety in vertebrates. In the current study, we evaluated the effects of long-term TS on four-member groups of male Nile tilapia, a worldwide reared species whose socially aggressive behavior is an essential source of stress. We placed a rectangul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Nevertheless, one possible mechanism that explains the effect of TS on productive parameters is the reduction in aggressive interaction. In previous studies with Nile tilapia, we showed that TS decreases aggression in both isolated [25] and grouped animals [26]. Aggressive interactions, in turn, demand high energy expenditure for fish [48], which can interfere with growth in Nile tilapia [49].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Nevertheless, one possible mechanism that explains the effect of TS on productive parameters is the reduction in aggressive interaction. In previous studies with Nile tilapia, we showed that TS decreases aggression in both isolated [25] and grouped animals [26]. Aggressive interactions, in turn, demand high energy expenditure for fish [48], which can interfere with growth in Nile tilapia [49].…”
Section: Discussionmentioning
confidence: 80%
“…Both apparatuses, each in their respective treatments, were introduced in the middle of the glass tank (Figure 1C); thus, when passing through the center of the glass tank, the fish in the TS treatment had contact with the silicone bristles (Figure 1D). The TS apparatus does not remove the mucus lining the bodies of animals, nor does it cause injury [25,26,31]. Moreover, Nile tilapia individuals spontaneously cross through this apparatus and overcome an aversive stimulus to access it [31], meaning it is not aversive to the fish.…”
Section: Tactile Stimulationmentioning
confidence: 99%
See 3 more Smart Citations